The Syncretization of Sunan Kalijaga Teachings: A Structuralism Study In Determining Qibla Direction of Demak Great Mosque - Fairuz Sabiq (Millati: Journal of Islamic Studies and Humanities, 2021)
The history of the spread of Islam in Java was carried out by the sunans or known as walisongo. They spread and develop Islam with various methods and without violence, so that Islam can be accepted by the community and become the religion of the majority of the Javanese population. One of the walisongo who taught and developed Islam in Java with the method of syncretization or acculturation between culture and Islam religion was Sunan Kalijaga. The syncretization of Sunan Kalijaga’s teachings is a propaganda medium that has succeeded in attracting people to adhere to Islam. Sunan Kalijaga built a mosque that combines Islamic culture and teachings. He also determined the qibla direction of the Great Mosque of Demak by combining Islamic teachings with Javanese culture. Sunan Kalijaga’s determination of the Qibla direction is by raising the right hand holding the Ka’ba (symbol) and the left hand (silent) holding the mustoko of the Demak mosque. If studied from Levi-Strauss Structuralism, it will be clearly seen the true meaning or message of the syncretization of Sunan Kalijaga’s teachings of the Qibla direction. One of the meanings or messages is that the determination of the Qibla direction can be done with the medium of the shadows of the Sun. Currently, this method is known as ras}dulqiblah.